Lithium levels in Peninsular Malaysian coastal areas: an assessment based on mangrove snail Nerita lineata and surface sediments - Cheng, Wan Hee; Yap, Chee Kong; Zakaria, Mohamad Pauzi; Aris, Ahmad Zaharin; Tan, Soon Guan (Universiti Putra Malaysia Press, 2015)
Sampling for the mangrove snails, Nerita lineata, and surface sediments was carried out from nine geographical sites of Peninsular Malaysia in April 2011. The concentrations of Lithium (Li) were determined in the shells, opercula and soft tissues of N. lineata and in the surface sediments by using ICP-MS. The ranges of Li concentrations (µg/g dry weight) were found to be 0.107-0.283 for shells, 0.021-0.177 for opercula and 0.011-0.634 for total soft tissues of N. lineata. For sediments, Li ranges were found to be between 21.84- 146.22 µg/g dry weight). The distribution of Li was found to be: sediment> ST> shell> opercula. The Li sediment data in the present study were comparable with the results of Li contaminated sediments which had been previously reported in the literature and higher than those of continental crust materials and igneous rocks. There was no significant correlation (P>0.05) for the Li levels between the sediments. The snails (shells, opercula and soft tissues) and this indicated that Li is an essential metal for metabolism and thus is being regulated in the body of the snail.